Research and application of time-varying law of anchoring force of split-set bolt based on field measurement - Hao, Yingjie; Zhu, Mingde; Wang, Chunlong; Yin, Yantian; Hou, Kuikui; Huang, Peng (Frontiers in Environmental Science, 2023)
Split-set bolt is widely used in supporting stope and roadway surrounding rock in metal mines. The maximum pull-out force generated by the relative slippage between the anchor bolt and the drill hole can serve as an indicator for assessing its anchoring force, and the anchoring force of the grouted anchor bolt exhibits certain regularity over time. This pull-out test was carried out at different time points after the construction of the split-set bolt by using the drawing equipment, and the variation law of its anchoring force with time was studied. The anchoring force on per unit area of surrounding rock is selected as a evaluation parameter, and the reinforcement support scheme of surrounding rock is optimized from the aspects of stress release of surrounding rock in the initial stage of excavation and stability of anchoring force on per unit area of surrounding rock. The convergence monitoring measurement method of roadway surrounding rock is adopted, and the same bolt drawing area is selected to verify the feasibility of the reinforcement support scheme. The effectiveness of the reinforcement scheme is verified by monitoring and comparing the roof subsidence and the lateral convergence of two walls between two different support schemes.